Professed religious affiliation and the practice of euthanasia. - Baume, P (1995)
Attitudes towards active voluntary euthanasia (AVE) and physician-assisted suicide (PAS) among 1,238 doctors on the medical register of New South Wales varied significantly with self-identified religious affiliation. More doctors without formal religious affiliation ('non-theists') were sympathetic to AVE, and acknowledged that they had practised AVE, than were doctors who gave any religious affiliation ('theists'). Of those identifying with a religion, those who reported a Protestant affiliation were intermediate in their attitudes and practices between the agnostic/atheist and the Catholic groups. Catholics recorded attitudes most opposed to AVE, but even so, 18 per cent of Catholic medical respondents who had been so requested, recorded that they had taken active steps to bring about the death of patients.